HUBUNGAN KEKERASAN VERBAL ORANG TUA DENGAN PERKEMBANGAN EMOSIONAL REMAJA SMPN 6 SUBANG - Auralya, Shifa; Prathama, Reggi; Nurfajriyani, Ika (Juru Rawat. Jurnal Update Keperawatan, 2025)
Verbal abuse is a common form of violence within the family environment. Verbal abuse by parents can negatively impact the emotional development of adolescents. It can hinder emotional growth, such as  decreasing self-confidence, increasing anxiety, and causing difficulties in emotional regulation and social  relationships. If left unaddressed, this condition may lead to long-term mental health problems in adolescents.  This study aims to examine the relationship between parental verbal abuse and the emotional development of  adolescents at SMPN 6 Subang. This research employed a descriptive correlational design with a cross sectional approach. The sample consisted of 107 adolescents selected using purposive sampling and stratified  random sampling techniques. Data were collected using questionnaires on parental verbal abuse and  adolescent emotional development, and analyzed using the Spearman Rank correlation test. There is a significant relationship between parental verbal abuse and adolescent emotional development (p value = 0.000 < 0.05). This relationship is strongly negative, as indicated by a correlation coefficient of r = 0.674. These findings suggest that higher levels of verbal abuse from parents are associated with poorer emotional development in adolescents. There is a significant negative relationship between parental verbal abuse and the emotional development of adolescents. The more severe the verbal abuse, the poorer the emotional development of adolescents.